Human Rights and Voluntary Repatriation in International Law: Legal Challenges in Addressing Rohingya Refugees in Indonesia - Ridwan Arifin; Fitria Damayanti; Izan Mateo Cassandro; Christina Noelia Umbría (International Law Discourse in Southeast Asia, 2026)
The existence of Rohingya refugees in Indonesia today has caused various polemics, especially Indonesia’s position as a transit country that has not ratified related conventions so that there is no obligation to accept refugees in Indonesia. The presence of refugees in Indonesia that causes conflict makes Indonesia's position at a crossroads to fulfill international obligations or fulfill obligations to its citizens so that they do not experience anxiety about their safety of life. This research aims to first explain the arrangements and conditions of repatriation for refugees in international law. Second, analyze Indonesia’s obligations under international law as a transit country for Rohingya refugees. Third, analyze the relationship between Indonesia's international obligations and domestic policies in the repatriation of its Rohingya refugees. This research applies a type of qualitative legal research with a juridical-normative approach. This research uses primary, secondary and tertiary legal materials as study materials. This research produced several findings, namely first, the practice of repatriation is the process of returning refugees to their country of origin after moving to a transit country or a third country. UNHCR as an extension of the United Nations has been operating in Indonesia since 1979. Second, Indonesia has tried to maintain the lives of refugees who choose Indonesia as a transit country. According to UNHCR, at the end of 2023, there were 12,295 refugees registered with UNHCR in Indonesia. As a transit country, refugee reception in Indonesia is based only on humanity. Third, the application of the concept of dualism makes Indonesia position itself that international law and national law are separate legal systems, and do not have a relationship of superiority or subordination to each other.